2012
DOI: 10.2139/ssrn.1023523
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital, Industrial Growth and Resource Curse

Abstract: How the country's natural resource abundance affects the industrial growth? We argue that one of the transmission mechanisms is via the accumulation of country's high skilled human capital. In particular, we empirically investigate whether link between country's natural resource endowment and industry-level growth depends on industry human capital requirement. We show that in the 1980s and the 1990s, industrial sectors that are high-skilled labor intensive developed disproportionately slowly in countries with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Negative GDP growth rates due to the rollback to the stationary level of per capita income for the country (by GDP per capita) Corden & Neary, 1982;Krugman, 1987;Matsuyama, 1992;Suslova & Volchkova, 2007 Europe ''Dutch disease'' (the Groningen effect) Strengthening of the national currency due to an increase in income from the export of raw materials '' Expenditure effect ''(or ''income use effect'') on the performance of the Nordic countries' disaggregated environmental taxes (Alola & Nwulu, 2022). The result posits the feasibility of Green growth in the panel of Nordic countries while a significant and negative nexus between GDP and energy intensity was also established.…”
Section: Overshooting Modelmentioning
confidence: 99%
“…Negative GDP growth rates due to the rollback to the stationary level of per capita income for the country (by GDP per capita) Corden & Neary, 1982;Krugman, 1987;Matsuyama, 1992;Suslova & Volchkova, 2007 Europe ''Dutch disease'' (the Groningen effect) Strengthening of the national currency due to an increase in income from the export of raw materials '' Expenditure effect ''(or ''income use effect'') on the performance of the Nordic countries' disaggregated environmental taxes (Alola & Nwulu, 2022). The result posits the feasibility of Green growth in the panel of Nordic countries while a significant and negative nexus between GDP and energy intensity was also established.…”
Section: Overshooting Modelmentioning
confidence: 99%
“…This is sometimes referred to as absorption and involves the spread, adoption, adaptation, and application of innovative "green" technology across and within countries. Through the use of alternative energy sources, green innovation and R&D investments may be seen as important drivers in the shaping of economic systems, particularly in the concept of "green economy" growth (Suslova and Volchkova, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, a few studies have found a link between natural resources, institutional quality, and the human capital. Those that have found a link suggest that high levels of oil production (and resulting incomes) coupled with weak institutions result in little opportunity to improve educational levels (Aljarallah, 2019;Suslova and Volchkova, 2012;Gylfason, 2001;Aron, 2000). Moreover, Bulte et al (2005) found that natural resources damage the institutional quality and then these institutions harm the human capital, thus resource rich countries tend to experience lower levels of human development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…About this role, Bravo-Ortega and De Gregorio (2005) assert that resource rich countries that have escaped the resource curse tend to have a higher human capital level. Suslova and Volchkova (2012) recommend developing educational policies that are directed towards a skilled labor force, as it is crucial to guarantee the economic development sustainability in resource rich nations. Accordingly, the significant role of the human capital in this study cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%